Half‐sandwich ruthenium, rhodium and iridium complexes featuring oxime ligands: Structural studies and preliminary investigation of in vitro and in vivo anti‐tumour activities. (11th October 2016) - Palepu, Narasinga Rao; Adhikari, Sanjay; J, Richard Premkumar; Verma, Akalesh K.; Shepherd, Samantha L.; Phillips, Roger M.; Kaminsky, Werner; Kollipara, Mohan Rao
Abstract : Half‐sandwich ruthenium, rhodium and iridium complexes (1 –12 ) were synthesized with aldoxime (L1 ), ketoxime (L2 ) and amidoxime (L3 ) ligands. Ligands have the general formula [PyC(R)NOH], where R = H (L1 ), R = CH3 (L2 ) and R = NH2 (L3 ). Reaction of [(arene)MCl2 2 ] (arene = p ‐cymene, benzene, Cp*; M = Ru, Rh, Ir) with ligandsL1 –L3 in 1:2 metal precursor‐to‐ligand ratio yielded complexes such as [(arene)MLκ 2 (N∩N) Cl]PF6 . All the ligands act as bidentate chelating nitrogen donors in κ 2 (N∩N) fashion while forming complexes. In vitro anti‐tumour activity of complexes2 and10 against HT‐29 (human colorectal cancer), BE (human colorectal cancer) and MIA PaCa‐2 (human pancreatic cancer) cell lines and non‐cancer cell line ARPE‐19 (human retinal epithelial cells) revealed a comparable activity although complex2 demonstrated greater selectivity for MIA PaCa‐2 cells than cisplatin. Further studies demonstrated that complexes3, 6, 9 and12 induced significant apoptosis in Dalton's ascites lymphoma (DL) cells. In vivo anti‐tumour activity of complex2 on DL‐bearing mice revealed a statistically significant anti‐tumour activity ( P = 0.0052). Complexes1 –12 exhibit HOMO–LUMO energy gaps from 3.31 to 3.68 eV. Time‐dependent density functional theory calculations explain the nature of electronic transitions and were in good agreement with experiments. Abstract : Half‐sandwich water‐soluble ruthenium, rhodium and iridium complexes (1 –12 ) were synthesized and characterized. Two complexes (2 and10 ) exhibited equipotent in vitro anti‐tumour activity against HT‐29 (human colorectal cancer), BE (human colorectal cancer) and MIA PaCa‐2 (human pancreatic cancer) cell lines. Complexes3, 6, 9 and12 induced apoptosis in Dalton's ascites lymphoma cells. The complexes possess hydroxyl group which imparts strong hydrogen bond donor ability.